Analisis Penerapan Pelayanan Publik Berbasis Online Dalam Revolusi Modern di Kantor BPN ( Badan Pertanahan Nasional ) Kabupaten Nagan Raya - Zuhrizal Fadhly; Bayukri Bayukri (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to analyze the online-based public services that are applied at the office of the National Land Agency in Nagan Raya Regency. The research carried out is to identify problems that occur in its application, in this study the method used is qualitative research with data collection using interview and interview methods. Documentation, the research results obtained are the application of online services at the Nagan Raya National Land Agency office is fairly good but still not optimal due to various factors that influence it, such as (1) Nagan Raya people who do not master technology, (2) inadequate internet network. on location, and (3) Application Systems that often experience Constraints